Quantitative evaluation of microleakage in class V cavities using one-bottle and self-etching adhesive systems Avaliação quantitativa da microinfiltração em cavidades classe V utilizando sistemas adesivos de frasco único ou autocondicionante - Fabiana Mantovani Gomes França; Flávio Henrique Baggio Aguiar; Alex José Souza dos Santos; José Roberto Lovadino (Sociedade Brasileira de Pesquisa Odontológica, 2004)
The aim of this in vitro study was to evaluate quantitatively the microleakage in class V cavities restored with one-bottle and self-etching adhesive systems with and without previous acid etching. Two one-bottle adhesive systems (Single Bond and Prime & Bond 2.1) and one self-etching adhesive system (Clearfil Mega Bond) were used in this study. One hundred and twenty sound human premolar teeth were randomly divided into 6 groups, and 20 class V restorations were prepared in the root dentin to test each bonding system. Each bonding system was used with and without acid etching. Specimens were prepared, dyed with 2% methylene blue, sectioned, triturated, and evaluated with an absorbance spectrophotometer test in order to quantify the infiltrated dye. Results were statistically evaluated by ANOVA and Tukey-Kramer test. No statistically significant differences were found among the adhesive systems when no etching agent was used. However, the Single Bond adhesive system showed statistically significant lower microleakage means than Clearfil Mega Bond and Prime & Bond 2.1 when 37% phosphoric acid was used. Single Bond and Clearfil Mega Bond adhesive systems presented similar behavior when the manufacturers' instructions were followed. O objetivo deste estudo in vitro foi avaliar quantitativamente a microinfiltração em cavidades classe V restauradas com a utilização de sistemas adesivos de frasco único e autocondicionante com e sem a realização de condicionamento ácido prévio. Dois sistemas adesivos de frasco único, Single Bond e Prime & Bond 2.1, e um sistema adesivo autocondicionante, Clearfil Mega Bond, foram utilizados. Cento e vinte pré-molares humanos hígidos foram divididos em seis grupos, e vinte restaurações classe V foram preparadas na dentina radicular para avaliar cada sistema adesivo. Cada sistema adesivo foi utilizado com e sem condicionamento ácido. Os espécimes foram preparados, corados com azul de metileno a 2%, seccionados, triturados e avaliados em espectrofotometria para quantificar o corante infiltrado. Os dados foram submetidos a ANOVA e ao teste de Tukey-Kramer. Nenhuma diferença estatística significativa foi encontrada entre os sistemas adesivos quando o condicionamento ácido não foi utilizado. No entanto, o sistema adesivo Single Bond demonstrou menores médias de microinfiltração comparadas às médias dos sistemas adesivos Clearfil Mega Bond e Prime & Bond 2.1 quando o condicionamento com ácido fosfórico a 37% foi utilizado. Os sistemas adesivos Single Bond e Clearfil Mega Bond demonstraram o mesmo comportamento quando as recomendações do fabricante foram seguidas.